Inklusi Budaya dalam Aturan Perpajakan Indonesia - Cheisviyanny, Charoline; Tanno, Aries; Suhanda, Suhanda (Universitas Negeri Padang, 2025)
Tax compliance is the most complex tax issue. Previous studies have found many factors that influence tax compliance, one of which is cultural factors. This study analyzes cultural inclusion in Indonesia’s tax regulations by using Literature Review approach. The result shows that the government has paid attention to the diversity of cultures and local wisdoms in Indonesia by integrating them into tax regulations, but has not optimally utilized to improve tax compliance. It suggests utilizing the collective culture in the implementation of a cultural approach to improve tax compliance.